Reducing distracted pedestrian behavior using Bluetooth beacon technology: A crossover trial. (September 2021) - Schwebel, David C.; Hasan, Ragib; Griffin, Russell; Hasan, Raiful; Hoque, Mohammad Aminul; Karim, Md. Yasser; Luo, Kevin; Johnston, Anna
Highlights: Pedestrian injuries are increasing, partly due to distracted pedestrian behavior. We evaluated StreetBit, a mostly-passive primary prevention program. StreetBit alerts distracted pedestrians directly on their smartphones. Oft-distracted pedestrians with full-screen alerts had sharply reduced distraction. StreetBit offers promise and warrants continued development and empirical testing. Abstract: Background: The number of fatal pedestrian injuries in the United States has steadily increased over the past decade. Multiple factors likely contribute to this trend, but the growth of pedestrians distracted by mobile devices is widely hypothesized to play a major role. Existing strategies to reduce distracted pedestrian behavior are few and mostly ineffective. The present study evaluated StreetBit, a mostly-passive primary prevention program to reduce distracted pedestrian behavior by alerting distracted pedestrians directly on their smartphone when they approach an intersection, reminding them to attend to traffic as they crossed. Methods: 385 individuals who regularly crossed a target street corner at an urban university downloaded StreetBit on their phones and participated in a crossover design study whereby the app was inactive for 3 weeks (baseline behavior phase), actively provided alerts for 3 weeks (intervention phase), and then was inactive again for 4 weeks (post-intervention phase). User distraction while crossing the intersection was collected electronically for a total of 34, 923 street-crossing events throughout the 10-week study. Results: In crude (unadjusted) models, participant distraction was similar across all phases of the research; this result was maintained after adjusting for potential covariates as well as after conducting a sensitivity analysis limited to data from only week 3 of each study intervention phase. In a model stratified by phone/warning type and baseline distraction rates, Android phone users who received a warning that blocked the full screen and had a high baseline distraction rate (≥75% distracted crossings) had a 64% decreased odds of distraction during the alert phase (OR 0.36, 95% CI 0.25–0.51) and a 52% decreased odds of distraction during the post-intervention phase (OR 0.48, 95% CI 0.25–0.94). Users reported positive impressions about the StreetBit app in a post-intervention survey. Discussion: StreetBit, an innovative app designed to prevent distracted pedestrian behavior through a mostly-passive primary prevention strategy relying on intrusive reminders, proved effective among smartphone users who received a warning blocking the full screen and who were frequently distracted at baseline, but not among other users. The results appear to reflect the confluence of two influencing factors. First, due to software development limitations, visually-distracted Android users received a highly intrusive app warning that blocked their smartphone screen whereas iOS users received a less intrusive banner notification blocking a small upper portion of the screen. Second, most users were curious to see if the app was functioning properly, creating artificially-inflated estimates of distraction as users purposefully watched their phones when crossing. Thus, our results indicate promise for StreetBit as an effective intervention and warrant continued software development and empirical testing.